Rhodothermus bifroesti sp. nov., a thermophilic bacterium isolated from the basaltic subsurface of the volcanic island Surtsey. - Pauline Bergsten (11810319); Pauline Vannier (4535077); Alan Mougeolle (11810767); Louise Rigaud (11810772); Viggó Thór Marteinsson (11810775) (2022)
Supplementary Data For Rhodothermus bifroesti sp. nov., a thermophilic bacterium isolated from the basaltic subsurface of the volcanic island Surtsey as published in International Journal of Systematic and Evolutionary Microbiology. Annotated genes from genome of Rhodothermus bifroesti strain ISCAR-7401 T RASTtk, v1.073, Kbase (Annotate Genome/Assembly)